anonymous
  • anonymous
Solve this equation\[\sin^6 x+\cos^6 x=\frac{5}{8}\]for \(x \in[0,2\pi]\)
Meta-math
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
sin^6 x + cos^6 x (sin^2x)^3+(cos^2x)^3 (sin^2x + cos^2x) (sin^4x-sin^2x cos^2x +cos^4x) 1*{(sin^2x +cos^2x)^2 -3sin^2x cos^2x} 1-3sin^2xcos^2x 1-3(sinx cosx)^2 1-3(sin2x/2)^2 1-3/4 sin^2(2x)
anonymous
  • anonymous
1-3/4 sin^2 (2x) =5/8 3/4 sin^2 (2x)=3/8 sin^2 (2x)=1/2 2sin^2 (2x) =1 1-2sin^2 (2x)=0 cos4x=0
anonymous
  • anonymous
Now LET a=4x then, cos(a)=0 , 0<=a<=8pi

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Solve for a
anonymous
  • anonymous
I hope this will lead to the solution.
anonymous
  • anonymous
And remember x=a/4
anonymous
  • anonymous
Is that correct @mukushla
anonymous
  • anonymous
nice job :)
anonymous
  • anonymous
i think if you do it like this it would be shorter \[ (1-\cos^{2}x)^{ 3}\]\[(1-\cos^{2}x)^{ 3} +\cos ^{6}x=\frac{ 5}{ 8 }\] \[1-\cos ^{6}x-3\cos ^{2}x(1-\cos ^{2}x)+\cos ^{6}x=\frac{ 5 }{ 8 }\] the two cos^6 terms cancel \[-3\cos ^{2}x \times \sin ^{2}x=\frac{ 5 }{ 8 }-1\] \[3\sin ^{2}x \times \cos ^{2}x=\frac{ 3 }{ 8 }\] multiply both sides by 4/3 and we have\[4\sin ^{2}xcos ^{2}x=\frac{ 1 }{ 2 }\] and 2sinx cosx=sin2x so \[\sin ^{2}2x=\frac{ 1 }{ 2 }\] hence \[2x=\frac{ \pi }{ 4 } or 2x=\frac{ 3\pi }{ 4 }\] hence x is pi/8 or 3pi/8
anonymous
  • anonymous
it is looking cumbersome but if you work it out it wont be so.........

Looking for something else?

Not the answer you are looking for? Search for more explanations.